CONCEPT OF THE ENGLISH LANGUAGE TRAINING OF AIR NAVIGATION SERVICE PERSONNEL - Petrashchuk, Olena (Proceedings of National Aviation University (archive), 2012)
The article deals with the Concept of English language training of Air Navigation Service personnel, which is proposed for providing quality language training of the specialists. The proposed Сoncept is in tune with the up to date approach to vocational training (ICAO TRAINAIR PLUS) which prioritizes an employer’s expectations then the standard educational programme.